The Implementation of Synergetic Teaching Learning Strategies to Imrpove the Learning Outcomes of Fiqh Subject at Mts Al-Washliyah Pancur Batu - Agustina, Dwi; Sinaga, Ali Imran (Al'Adzkiya Journal, 2023)
The problem of this study was the students were found to be less active due to the inappropriate learning strategies used by the teacher. It made students feel bored and caused the learning outcomes not to meet the minimum proficiency criteria. This research was quantitative research with experimental type. The sample in this study was 25 students of MTs Al-Washliyah Pancur Batu, taken with a quasi-experimental design or non-random sampling technique. This study aimed to determine how much influence the implementation of the Synergetic Teaching learning strategy had in improving Fiqh learning outcomes in class VII students of MTs Al-Washliyah Pancur Batu. A synergetic Teaching learning strategy is a learning strategy that combines two different learning activities. This strategy allows students to share learning outcomes from the same material by comparing notes. As for the results of this study, it obtained that the product-moment correlation was rxy = 0.838 which indicated a reasonably high correlation. The Alternative Hypothesis (Ha) of